The Transformation Of Participants Through The Application Of Islamic Principles In The Muhammadiyah Yogyakarta Pension Fund - Indah, Nur; Ilyas, Hasnawati; Miftachul Ulum, Kefi (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
The intention of building contracts in Islamic financial institutions is to avoid contracts that are governed by common laws. Now, all institutions, whether an Islamic bank or an Islamic non-bank, are required to enact contracts in each transaction or agreement made by contracting parties, meaning a mutually acceptable, binding, voluntary agreement. This study investigates the implementation of contracts at the Muhammadiyah Yogyakarta Sharia Pension Fund—an example of a non-bank Islamic financial institution in Indonesia—abiding by sharia contracts according to the OJK Regulation No. KEP-02/D.05/2019 and Muhammadiyah Yogyakarta Sharia Pension Fund Regulation No. KEP-65/NB.21/2022. Article 6 mentions the contents of various contracts, including Hibah bi Syarth, Hibah Muqayyadah, Wakalah, Wakalah bil Ujrah, Mudarabah, Ijarah, and other contracts aligned with the guidelines of DSN-MUI. This research further analyses the challenges of compliance in contract application and operations after the introduction of the sharia system. The study employs descriptive analysis using a field research approach with a juridical empirical study on regulation governing Islamic pension fund agreements. Other than using interviews and observations, the study will also adopt field documentation at Muhammadiyah Yogyakarta Sharia Pension Fund. According to current findings, contracts find application in both oral and written forms, although some officials do not know that their acts are actually contractual agreements. Contracts are conducted according to the stated regulations. The greatest challenge relates to asset transformation into sharia-compliant forms and the deepening of personnel understanding on the application of contracts. The study calls for institutional efforts aimed at enhancing compliance and competency of employees in the implementation of sharia-based contracts as operational alignment with the tenets of Islam